RASIONALITAS PERDANA MENTERI BORIS JOHNSON MENYEPAKATI PERJANJIAN DAGANG INGGRIS-UNI EROPA PASCA REFERENDUM BREXIT - Hafid Adim Pradana; Syelda Titania Sukarno Putri (Journal of International Relations, 2022)
This research is structured to explain Boris Johnson's rational action in agreeing a post-Brexit trade agreement. Following the 2016 referendum and David Cameon's resignation as prime minister, Theresa May was replaced by Theresa May. During Theresa May's time, Brexit did not get resolved, so May resigned and was replaced by Boris Johnson. At the beginning of his term, Johnson attempted to resolve Brexit by any means including no-deal, however, it was so different when in 2020, Johnson actually took action to agree a post-Brexit trade agreement with the European Union after his Brexit proposal was rejected several times by the British parliament. Therefore, the author uses Rational Choice Theory. The data collection technique used in this study is a literature review from journals, official websites, and books which results that Johnson's rationality aims to save the British national economy and save the existence of Johnson's leadership as British prime minister. Johnson was then faced with the protracted Brexit issue so that he was faced with various policy alternatives from the European Union and the British Parliament. After considering various policy alternatives, Johnson succeeded in establishing a post-Brexit trade policy called the Withdrawal Agreement Bill in December 2020 which contained eight important points of trade cooperation. Keywords: Boris Johnson, Brexit, European Union, Rational Choice